SOSIALISASI PENGGUNAAN METODE PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI KELOMPOK A TK YAPIS MERAUKE - Christiana Normalita De Lima; Dharma Gyta Sari Harahap; Beatus Tambaip (BADAN PENERBIT STIEPARI PRESS, 2022)
Community Service aims to provide socialization to teachers at YAPIS Merauke Kindergarten about learning methods that can improve fine motor skills in early childhood, especially group A. This community service activity was attended by 11 Yapis Merauke Kindergarten teachers. The socialization of this service provides the benefits of knowledge to teachers about the types of learning methods that can improve the fine motor skills of early childhood including the Demonstration Method, Coloring Method, Play Method, Work Tour Method and Project Method. This service is expected to be able to provide new knowledge to teachers so that later it can be applied in the learning process in improving the fine motor skills of early childhood, especially group A